Development of a simple process to obtain luminescent YVO4:Eu3+ nanoparticles for Fiber Optic Dosimetry - Mentasti, Luciana (2020)
YVO4:Eu3+ is a red emitter phosphor commercially available as micrometric powder due to its high luminescence efficiency under electron-beam excitation. Although some published results have demonstrated the potential of using this micrometer material in Fiber Optic Dosimetry systems, there is no information regarding its use on a nanometric scale. In order to obtain a nanometric material with high luminescent efficiency, a simple synthetic combustion method was developed and the results were compared with both, those of a commercial material and those obtained by a typical coprecipitation synthesis. A single crystalline phase was obtained when the combustion route was employed for the preparation meanwhile two crystalline phases were obtained via coprecipitation synthesis. The particle size of YVO4:Eu3+ obtained by combustion route ranges from 55 up to 200 nm. Fourier Transform Infrared Spectroscopy and Thermogravimetric Analysis indicated that annealing at 600 °C promote the degradation of the impurities that remained adsorbed onto nanoparticles surface after the synthesis. However, to improve the Radioluminescence intensity, an annealing process at 1000 °C was required. The method allows obtaining a nanometric material with a scintillation intensity almost twice higher than that of the commercial powder.